An IGA based nonlocal gradient-enhanced damage model for failure analysis of cortical bone. (1st October 2021) - Soni, Aakash; Negi, Alok; Kumar, Sachin; Kumar, Navin
Highlights: A gradient enhanced nonlocal damage model under the framework of IGA is used to examine the fracture mechanism of a bovine cortical bone. The decreasing interaction domain approach reduces the spurious damage growth during the later stages of loading. The proposed model is capable of giving accurate and mesh-independent results for different modes of fracture. The material anisotropy of cortical bone has a significant impact on the fracture process. Abstract: The fracture behavior of a cortical bone is significantly affected by its hierarchal structure and a high degree of material anisotropy. Recently, continuum damage models have proven to be an effective tool to characterize such kind of material behavior. However, these models suffer from drawbacks such as mesh dependency, spurious damage growth, and incorrect prediction of damage initiation during the initial stage of loading process. To this end, the objective of this work is to develop a nonlocal gradient-enhanced damage model in an isogeometric setting to predict the fracture behavior of a cortical bone. The numerical framework is formulated considering an additional diffusion equation in conjunction with the standard equilibrium equation. The material is assumed to be transversely isotropic to incorporate the anisotropy in damage evolution. The versatility of the proposed framework is tested by solving problems for different modes of fracture. For numerical simulations, samples are taken from different quadrants of bovine cortical bone, and the effect of anisotropy on the damage characteristics of the bone are investigated.